2013
DOI: 10.3906/sag-1208-88
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of depression during the postpartum period and risk factors that affect the development of the depression

Abstract: In this study, the possibility of bread machine utilization as a quality control tool in the baking industry was investigated. Th ree diff erent fl our samples (F 1 , F 2 , and F 3 ) having diff erent protein contents were obtained and then 12% wheat starch and 2% vital gluten were added to these fl ours to adjust protein ratios. Th e physicochemical and rheological properties of these fl our combinations were analyzed. Specifi c volume, crumb grain attributes, crust and crumb color, and bread fi rmness in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These findings were in line with those of Rich-Edwards, who discovered that women in the youngest age group had nearly double the rate of depression scores as women in other age groups [ 17 ]. Housewives with lower incomes were more likely to score higher on the EPDS while Taşdemir et al [ 18 ] and Gumuş et al [ 19 ] both found consistent postpartum depression rates. According to a survey conducted by Dennis et al, poverty is the most important issue for housewives [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in line with those of Rich-Edwards, who discovered that women in the youngest age group had nearly double the rate of depression scores as women in other age groups [ 17 ]. Housewives with lower incomes were more likely to score higher on the EPDS while Taşdemir et al [ 18 ] and Gumuş et al [ 19 ] both found consistent postpartum depression rates. According to a survey conducted by Dennis et al, poverty is the most important issue for housewives [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional file 1. Table of features of the studies included in the systematic review [61][62][63][64][65][66][67][68][69][70].…”
Section: Supplementary Informationmentioning
confidence: 99%